ANALISIS SINKRONISASI KEBIJAKAN PEMERINTAH DAERAH BALI DAN BANYUWANGI DALAM MENDUKUNG IMPLEMENTASI PROGRAM PEMBANGUNAN PARIWISATA TERINTEGRASI DAN BERKELANJUTAN (P3TB) DI WILAYAH DESTINASI WISATA 3B - Bahreisy, Afghani Mahmuda; Azzahra, Kharisma Putri; Dewi, Nova Purnama; Khairiah, Nur Ainun; Rahmafitria, Fitri (Jurnal Pariwisata Indonesia, 2024)
Policy synchronization across regions is a key element in supporting the successful implementation of the Integrated and Sustainable Tourism Development Program (P3TB) in the 3B Tourist Destination area, which includes Banyuwangi, West Bali, and North Bali. This program aims to create tourist destinations that not only prioritize visitor numbers but also consider social, cultural, and environmental sustainability. This study analyzes the extent to which policies in each region, particularly those of Banyuwangi, Jembrana, Buleleng, and Bali Province, can be harmonized to achieve integrated tourism development goals. Policy synchronization plays a vital role in ensuring the harmonious management of natural resources, infrastructure development, community empowerment, and cultural preservation across the three regions. The study's findings indicate that policy synchronization in the 3B area effectively supports environmental conservation by managing sensitive areas such as Ijen Crater and West Bali National Park, preserving their tourist appeal without compromising local ecosystems. Additionally, harmonized policies facilitate integrated cross-regional infrastructure planning, such as the development of Ketapang-Gilimanuk Port, enhancing connectivity and accessibility for tourists. Synchronized community empowerment policies significantly contribute to increasing local community participation, generating direct economic benefits, and maintaining social and cultural balance. However, this study also highlights major challenges, including differences in development priorities between regions, imbalances in infrastructure development, and the need for stronger cross-sectoral coordination. The study recommends strengthening collaboration between central and regional governments, as well as other stakeholders, to ensure a more effective and sustainable implementation of P3TB. With these strategic steps, the 3B Tourist Destination area holds great potential to become a model of integrated tourism that is not only globally competitive but also inclusive for local communities and environmentally friendly.